RECONSTRUCTION OF TEACHER’S IDENTITY: A SOCIO-ANTHROPOLOGICAL STUDY OF THE JAVANESE SOCIETY - Sadam Fajar Shodiq; Syamsudin Syamsudin (Jurnal Cakrawala Pendidikan, 2019)
Teachers, according to the Javanese’s views, are those having a respectable position because they become the reference and role model for the Javanese. A teacher is considerably responsible for all students’ behaviors, both in and outside the classroom. In this digital era, this condition has shifted due to the occurrence of socio-anthropological changes in society. Although teachers’ identity shifts, they are still crucial in transferring values during the learning process. This study aimed to comprehensively find out how the reconstruction of teacher’s identity was carried out in socio-anthropologically changing situations among the Javanese, derived from 30 respondents. Qualitative research was then used in this study using the ethnographic method, and the subject of the research was Javanese. Data collection was performed through interviews using a purposive selection of respondents. Analysis techniques comprised of data collection, data selection, data presentation, and conclusion. As a result, it was found that, in the context of the Javanese, socio-anthropology in modern technology had affected the meaning of the teacher’s identity. Although the Javanese considered teachers as an ordinary profession and had the same level with other professions, the Javanese still held that teacher was an honorable profession and it deserved to be appreciated since the presence of a teacher could improve students’ knowledge.